2011
DOI: 10.5402/2011/839149
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone, Endothelial Health, and Erectile Function

Abstract: Experimental and clinical studies have reported that testosterone has a critical role in the maintenance of homeostatic and morphologic corpus cavernosum components, essential for normal erectile physiology. Although the exact mechanisms mediated by testosterone in erectile function are still under investigation, recent research has suggested an important role in the regulation of endothelial cell (EC) biological functions. Besides stimulating the production of EC mediators, testosterone is also thought to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 87 publications
1
23
0
Order By: Relevance
“…These data are corroborated by previous research demonstrating a reduction on plasma testosterone in diabetic models, which was also restored to normal levels by insulin replacement therapy [Tesone et al, 1980;Xu et al, 2014]. It was also shown that androgens may play a role in EPCs modulation and EC function [Foresta et al, 2008;Castela et al, 2011]. Although no alterations in PB EPCs were observed after insulin treatment, the decrease in endothelial damage may also be related to a testosterone protective effect in vascular endothelium.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These data are corroborated by previous research demonstrating a reduction on plasma testosterone in diabetic models, which was also restored to normal levels by insulin replacement therapy [Tesone et al, 1980;Xu et al, 2014]. It was also shown that androgens may play a role in EPCs modulation and EC function [Foresta et al, 2008;Castela et al, 2011]. Although no alterations in PB EPCs were observed after insulin treatment, the decrease in endothelial damage may also be related to a testosterone protective effect in vascular endothelium.…”
Section: Discussionsupporting
confidence: 86%
“…EPCs reside within the bone marrow (BM), and are mobilized to the peripheral circulation and recruited to vascular insult sites, where they differentiate into mature ECs, integrating, and repairing damaged vasculature [Asahara et al, 1999]. These processes are regulated by many factors, including Stromal cell-Derived Factor-1 alpha (SDF-1a), which by binding CXCR-4 [Tzeng et al, 2011;Suarez-Alvarez et al, 2012], play a relevant role in BM homeostasis, and progenitor cells (PCs) trafficking [Urbich and Dimmeler, 2004] and androgens, which may modulate EPCs functions [Foresta et al, 2008;Castela et al, 2011]. Furthermore, it has been suggested that a good glycemic control, besides improving endothelial function and reducing oxidative markers [Fadini et al, 2011], and may also increase circulating EPCs (cEPCs) [Hortenhuber et al, 2013].…”
mentioning
confidence: 99%
“…Importantly, TT, FT and BT levels correlated positively with IIEF‐15 score, which is a widely used, multi‐dimensional, self‐reporting tool for the assessment of ED and for the diagnostic evaluation of ED severity (Rosen et al ., ). The exact mechanism underlying the effect of testosterone on ED is not known (Castela et al ., ); however, a threshold level of testosterone is considered necessary for normal erectile function (Shabsigh et al ., ). Hypogonadism may also play an important role in the pathophysiology of ED, and TRT in combination with phosphodiesterase type 5 (PDE5) inhibitors has proven to be effective in hypogonadal men with ED (Shabsigh et al ., ; Foresta et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypogonadism and ED are the most common disorders observed in the ageing male (Castela et al ., ), which was our study population. A testosterone decline has also been associated with chronic medical diseases such as metabolic syndrome, diabetes mellitus and cardiovascular disease, which are conditions with an increased morbidity and mortality (Jones, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation